Mathematics as a Tool for Critical Citizenship: The Case of the Philippine National Elections 2022 - Briones, Jeric C. (Archīum Ateneo, 2024)
This paper showcases an example of how mathematics was utilized to debunk a suspected anomaly in election returns in the aftermath of the Philippine national elections last May 2022. Initial results of the automated elections yielded numbers that the public deemed suspicious. In response to a call for experts' opinions on the matter, we processed and analyzed large samples of preprocessed data to which we have been given access. Using data analytics techniques, we examined transmission arrivals of election returns and compared them against the total votes transmitted, with the analysis performed at different aggregation levels. Our analyses showed that the seemingly suspicious numbers can be explained by examining the distributions of the transmission arrivals of election returns and analyzing those distributions using different levels of aggregation. From the perspective of critical mathematics education (CME) particularly, focusing on mathematics for critical citizenship, we highlight the importance of mathematics to help fight disinformation and spread of unfounded rumors. The paper concludes with recommendations for enriching students' mathematical experiences that could pave the way for a responsive and engaged citizenry in our country.